Estudio de prefactibilidad para la instalación de un servicio a gran escala de comida saludable bajo el modelo de aprovisionamiento MRP - Acosta Osorio, Ronald German (2021)
The thesis started by knowing the main problems in food establishments, in order to determine the general objective where the implementation of this project would be evaluated as an alternative solution. The composition of the main product, the orders, is taken from the CENAN balanced plate model. The analysis of the macro-environment allowed us to know the influence of external factors on Peruvian companies, added to the impact of COVID-19. Likewise, the internal sector was analyzed to understand the forces that influence its profitability. The demand for the last year of the project was calculated at 82,720 orders and the choice of location resulted from the evaluation of the most relevant location factors added to the new consumer habits, resulting in the C.C. Jockey Plaza. For the dimensioning of the service, the size of the market, resources, technology and the breakeven point (230 orders / day) were analyzed, obtaining a size of 234 orders / day. The installed capacity was calculated by identifying the requirements: labor and equipment. For the requirement of inputs, the letter, the packaging and the caloric content were evaluated. The production environment is by make to stock and provisioning following the MRP model. The type of company Closed Anonymous Society will be chosen, as well as the MYPE Tributary, a regime that will help in the payment of taxes and labor benefits. The financial and economic evaluation with a COK of 14.31%, obtaining a financial NPV of S / 158,628 and an IRR of 49.83%; an economic NPV of S / 105,551 and an IRR of 26.98%. The investigation culminates by publicizing the positive impact of the project on society, having an added value of S / 3,316,350.